1999
DOI: 10.1055/s-2006-960465
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Essential Oils ofOcimum canum,O. gratissimumandO. minimum

Abstract: The essential oils of OCIMUM CANUM, O. GRATISSIMUM and O. MINIMUM grown in S. Tomé, where they are used in Traditional Medicine mainly as febrifuge and for the treatment of respiratory diseases, were investigated. The essential oils were obtained from the aerial parts by hydrodistillation and subsequently analysed by GC, GC-MS and (13)C-NMR. (13)C-NMR SPECTROSCOPY proved to be an important tool, which can be very useful in the identification of most of the constituents. Major compounds in the volatile oil of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 3 publications
2
50
0
3
Order By: Relevance
“…Similar results were observed by Dubey et al (2000), who verified citral, ethyl cinnamate chemotype, eugenol, linalol as the dominant constituents of O. gratissimum essential oil. On the other hand, Martins et al (1999) did not find eugenol as constituent of the essential oil in O. gratissimum from Portugal Island.…”
Section: Discussionmentioning
confidence: 73%
“…Similar results were observed by Dubey et al (2000), who verified citral, ethyl cinnamate chemotype, eugenol, linalol as the dominant constituents of O. gratissimum essential oil. On the other hand, Martins et al (1999) did not find eugenol as constituent of the essential oil in O. gratissimum from Portugal Island.…”
Section: Discussionmentioning
confidence: 73%
“…The volatile oil of O. gratissimum also contain phenols, particularly thymol which was earlier reported to be responsible for the antimicrobial action [11,104]. The studies of the chemical composition of a related species O. suave showed that the major components of the oil are p-cymene, α-thujene, myrcene and thymol, in addition to phenols [105][106]. Therefore, these compounds may be responsible for the grains protectant and antimicrobial activities of the hexane fraction of O. gratissimum and it could serve as a potential source of pharmaceutical applications and in the control of agronomic pests.…”
Section: Resultsmentioning
confidence: 97%
“…[19][20][21][22][23] It was previously reported that the oil of O. basilicum contained linalool (69%) and eugenol (10%). 23 Linalool (45.7%) and eugenol (13.4%) were reported to be the main components of the previously analyzed materials.…”
Section: Discussionmentioning
confidence: 99%